2010
DOI: 10.1002/pssb.201000271
|View full text |Cite
|
Sign up to set email alerts
|

Study of Pd–Au/MWCNTs formic acid electrooxidation catalysts

Abstract: The Pd-Au multiwall carbon nanotubes (MWCNTs) supported catalyst exhibits higher power density in direct formic acid fuel cell (DFAFC) than similar Pd/MWCNTs catalyst. The Pd-Au/ MWCNTs catalyst also exhibits higher activity and is more stable in electrooxidation reaction of formic acid during cyclic voltammetry (CV) measurements. After preparation by polyol method, the catalyst was subjected to two type of treatments: (I) annealing at 250 8C in 100% of Ar, (II) reducing in 5% of H 2 in Ar atmosphere at 200 8C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 10 publications
(42 reference statements)
1
24
0
Order By: Relevance
“…This may results from poisoning of metal particles surface by oligomers formed during thermal treatment in reducing (H 2 ) atmosphere from adsorbed traces of ethyl glycol. This is in agreement with the observation [4,5] that the Pd and PdAu catalysts annealed in Ar after preparation by polyol method were completely inactive. The presence of carbon residues on Pd surface may explain the lower activity of PdAu4 in comparison with PdAu2 and PdAu3, in spite of smaller PdAu crystallites found in PdAu4 sample.…”
Section: Structural Properties By Xrd and Temsupporting
confidence: 92%
See 2 more Smart Citations
“…This may results from poisoning of metal particles surface by oligomers formed during thermal treatment in reducing (H 2 ) atmosphere from adsorbed traces of ethyl glycol. This is in agreement with the observation [4,5] that the Pd and PdAu catalysts annealed in Ar after preparation by polyol method were completely inactive. The presence of carbon residues on Pd surface may explain the lower activity of PdAu4 in comparison with PdAu2 and PdAu3, in spite of smaller PdAu crystallites found in PdAu4 sample.…”
Section: Structural Properties By Xrd and Temsupporting
confidence: 92%
“…Also, functionalised MWCNTs support decreases the agglomeration of metal nanoparticles and increases their dispersion. Recent studies on catalytic activity in formic acid electrooxidation of 17.8 wt%Pd/MWCNTs and 8.8 wt%Pd-10.0 wt%Au/MWCNTs catalysts prepared by an unmodified polyol method showed higher activity and stability for Pd-Au/MWCNTs [4,5]. The catalysts were active after reduction (5%H 2 /Ar, 200 o C), whereas inactive after annealing in ambient atmosphere (Ar, 250 o C).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The specific activity of Pd in the novel Au-Pd/MWCNTs catalyst was over two times higher than that on the Pd/MWCNTs catalyst. Mikolajczuk et al [97] found that the Pd-Au/MWCNTs catalyst exhibited higher activity and more stable in oxidation reaction of formic acid. The higher initial catalytic activity of Pd-Au/MWCNTs catalyst than Pd/MWCNTs catalyst in formic acid oxidation reaction was attributed to the electronic effect of gold in Pd-Au alloy [98,99].…”
Section: Pd Alloys Supported On Carbon Nanotubesmentioning
confidence: 99%
“…The carbon nanotubes (CNTs) 1 are characterized by their high specific surface area, good electrical conductivity, and access of reactants to the surface 2, and therefore their application as support for catalysts improves the catalytic performance. The Pd and Pd–Au on the multiwall carbon nanotubes (MWCNTs) supported catalysts have been recently studied 3–6. They have been found to be active in direct formic acid electrooxidation reaction for application in fuel cells (DFAFC) 3–6.…”
Section: Introductionmentioning
confidence: 99%